Global Rights and Local Struggles. The case of the ILO Convention n.189 on domestic work - Daniela Cherubini (Coordinamento SIBA, 2019)
In response to the promulgation of International Labour Organisation (ILO) Convention n.189 on domestic workers in 2011, scholars have turned their attention to this workforce, documenting how the Convention acted as a catalyst for the proliferation of campaigns at national, regional and international levels. The ILO Convention is an attempt to address domestic workers' labor rights as "global rights" and as a global common goal due to their implications at the level of human and social rights for a wide range of vulnerable subjects in many countries. However, little is known about the ways in which the Convention has been incorporated - or resisted - with respect to "local struggles" and in different local contexts. Our study contributes to filling this gap by offering a comparative analysis of four countries - Colombia, Italy, the Philippines and Taiwan - between 2011 and 2018. Considering Convention n. 189 as an exogenous factor, we explore the configurations of the strategic action field (Fligstein and McAdam 2012) of domestic workers' rights in these countries - including the actors involved, the focus of their action, the alliances they establish, and the frames they activate. Our analysis shows that Convention n. 189 seems to have fostered transformations in terms of mobilization and the enlargement of rights in contexts where it has promoted synergy between state and civil society actors, has been embedded in pre-existing local struggles and in larger progressive political projects, and has been framed in ways that touch on issues of national identity.